Rethrombolysis for Restruck Prosthetic Valve - Ezhilan, J (Nepalese Heart Journal, 2004)
One of the complications of prosthetic valve (PV) is thrombotic occlusion of the valve. The incidence is 5/100/yr overall and is more common in mitral position than in aortic position, PV thrombosis presentation can be acute due to thrombi (55%), Subacute due to thrombus and pannus (40%) and Chronic due to pannus alone (5%). It can manifest as congestive cardiac failure, Pulmonary embolism, cardiogenic shock, Thromboembolism or death. Conventionally it was treated with surgical thrombectomy and pannus excision or valve replacement. Later on thrombolysis was tried and various agents like Streplokinase, Urokinase and t- PA have been used successfully to lyse the thrombus.